2003
DOI: 10.1177/004051750307300111
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Static and Dynamic Drape Coefficients of Polyester Fabrics Through the Finishing Stages

Abstract: Static and dynamic drape behaviors of polyester woven fabrics are s died through representative finishing stages using two sets of fabrics with different conditions of relaxation and weight reduction. The node number n, the revolving drape increase coefficient Dr, and the dynamic drape coefficient Dd increase through the finishing stages, especially with relaxation. The static drape coefficient D, and revolving drape coefficient at 200 rpm D200 decrease through the finishing stages, especially with relaxation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Key words curve fitting, dynamic drapability, nonlinear logistic regression, tangent partition method sudaira and co-workers [4,5,[17][18][19]. They defined three stages when rotating the fabric from 0 to 240 rpm [4,5].…”
mentioning
confidence: 99%
“…Key words curve fitting, dynamic drapability, nonlinear logistic regression, tangent partition method sudaira and co-workers [4,5,[17][18][19]. They defined three stages when rotating the fabric from 0 to 240 rpm [4,5].…”
mentioning
confidence: 99%
“…The effect of high weight reduction ratio was observed with the decrease of D200 and increase of Dr. However, there were differences between samples A and B with respect to drape parameters, parameters at the final output (end of finishing stages) were similar [110].…”
Section: Fabric Finishingmentioning
confidence: 82%
“…These equations were applied in several further studies investigating drape in terms of studying different features of fabrics [57,[80][81][82][83] and the effect of finishing on fabric drape behaviour [92,110].…”
Section: DCmentioning
confidence: 99%
“…They analyzed also apart the static measuring the drapeability influenced with dynamical effect. They measured the dynamic drapeability during rotating the textile sample [1]. They found that the form of the draped sample is change from the dynamic effect.…”
mentioning
confidence: 99%